Accounting Information Use in Performance Based Compensation Systems (gjstudies, 2020)
This research investigates the nuanced and often overlooked role of accounting information within performance-based compensation systems, moving beyond traditionalagency theory frameworks to propose a novel, multi-dimensional model of informationutility. While extant literature predominantly treats accounting metrics as neutral,verifiable inputs for incentive alignment, this paper posits that their function is fundamentally interpretive, socially constructed, and contextually contingent. We arguethat accounting information does not merely measure performance but actively shapesit through three distinct, interlocking mechanisms: as a constitutive script that defineswhat ’performance’ means within an organizational narrative, as a relational tokenthat mediates power dynamics and trust between principals and agents, and as a cognitive frame that channels managerial attention and strategic choice. Our methodologyemploys a qualitative, longitudinal case study of a multinational corporation transitioning to a complex, multi-metric performance scorecard, combined with a computationalsimulation model that explores the emergent system dynamics of metric interactionover time. This hybrid approach allows us to capture both the rich, lived experienceof actors engaging with the compensation system and the systemic, often unintendedconsequences of metric interdependence. Findings reveal that the perceived fairnessand effectiveness of the compensation system are less dependent on the technical accuracy of the accounting metrics and more on their narrative coherence, their consistencywith informal organizational values, and their capacity to accommodate legitimate butunmeasured contributions. We identify a critical phenomenon termed ’metric myopiaconvergence,’ where agents and principals, despite conflicting interests, collaborativelynarrow their focus to a subset of manipulable, short-term accounting indicators, therebyundermining the long-term strategic goals the system was designed to promote. Thestudy concludes by proposing a shift from designing compensation systems based onmetric selection to designing them as adaptive information ecosystems, emphasizingtransparency in metric construction, forums for interpretive negotiation, and dynamicweighting mechanisms that respond to strategic evolution. This research contributesoriginal theoretical insights to management accounting, behavioral economics, and organizational theory by re-conceptualizing accounting information from a passive inputto an active, agential force in the performance management process